Projekt ładu europejskiego Williama Penna z 1693 r. - Robak, Piotr (Acta Universitatis Lodziensis. Folia Historica, 1995)
An Essay Towards the Present and Future Peace of Europe is a small political treatise published anonymously in London in 1693 when England was embroiled with France in the War of the League of Augsburg. William Penn (1644-1718), the author of this essay, was the English aristocrat, the member of the Quaker common named „Society of Friends” - one of the most radical puritan sect, and the founder of Pennsylvania in the North America. Penn proposed in his treatise to make real of the European League or the Imperial States as a way to establish a permanent peace on the Continent. He drew the plan of the Imperial or General Parliament of nations with the function of arbitration to solve the contentions or disputes between the states-signatories of the League. Penn considered that this international assembly will be gather in the appointed place and time and make decisions in the secret ballot. The sources of Penn’s project were in existing in the 17th century the European and American representative institutions, the earlier union propositions, the modern political philosophy and the Quaker pacifist ideas. Penn’s conceptions joined the proclamation of peace and justice in the international relations with the federal and parlimentary principles. However the solution was too much radical to find any reverberation on the European absolutist courts in the end of the 17th century. On the contrary, the most important meaning of An Essay... is in the evolution of the Quaker pacifism from the evangelical and spiritual views to the humanitarian and rational argumentation (integrational pacifism).